KINERJA STRUKTUR PEDIATRIC & ICCU BUILDING OF GUIDO VALADARES NATIONAL HOSPITAL MENGGUNAKAN PUSHOVER ANALYSIS - Oke, Matheus Putra Septian Seda; Hendrikus, Rani; Mooy, Merzy; Manubulu, Christiani Chandra; Bela, Krisantos Ria (Eternitas: Jurnal Teknik Sipil, 2024)
According to SNI 1726-2019, hospitals are in category IV building risk which has high factor importance for building planning against earthquakes. Therefore, an evaluation of buildings is needed which is not only affected by earthquakes but also the strength, stiffness, and ductility of the building itself. This study aims to produce the performance of the Guido Valadares National Pediatric Hospital and ICCU Building using pushover analysis. The results of the analysis show that there is a deviation failure caused by the presence of a ramp on one side of the building which results in greater stiffness on that side than on the other side of the building. A new structural system is applied on the lower side of the building with bracing reinforcement to create balance for the building. The new design results reveal better building structure performance and it is in accordance with applicable standards.